2022
DOI: 10.3390/nu14142965
|View full text |Cite|
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Promote NLRP3 Inflammasome Activation and Glomerular Endothelial Dysfunction in Diabetic Kidney Disease

Abstract: Diabetes mellitus is a metabolic disease largely due to lifestyle and nutritional imbalance, resulting in insulin resistance, hyperglycemia and vascular complications. Diabetic kidney disease (DKD) is a major cause of end-stage renal failure contributing to morbidity and mortality worldwide. Therapeutic options to prevent or reverse DKD progression are limited. Endothelial and glomerular filtration barrier (GFB) dysfunction and sterile inflammation are associated with DKD. Neutrophil extracellular traps (NETs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…A previous study showed that neutrophils isolated from diabetic humans and mice were primed to produce NETs ( 54 ). The increase of Biomarkers of NETs correlates with DKD severity, which NETs promote NLRP3 inflammasome activation and glomerular endothelial dysfunction under high glucose stress in vitro and in vivo ( 14 ). Additionally, neutrophils may also migrate into the kidneys of patients with DKD because their spontaneous adhesion increases ( 55 ), which is followed by abnormal activation and the secretion of proinflammatory cytokines, degranulation, and the release of reactive oxygen species ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that neutrophils isolated from diabetic humans and mice were primed to produce NETs ( 54 ). The increase of Biomarkers of NETs correlates with DKD severity, which NETs promote NLRP3 inflammasome activation and glomerular endothelial dysfunction under high glucose stress in vitro and in vivo ( 14 ). Additionally, neutrophils may also migrate into the kidneys of patients with DKD because their spontaneous adhesion increases ( 55 ), which is followed by abnormal activation and the secretion of proinflammatory cytokines, degranulation, and the release of reactive oxygen species ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, immune infiltrating cells mediated oxidative stress process is considered to play an important role in the occurrence and development of DKD ( 13 ). Animal experiments also showed that the number and activity of immune cells in the kidney are related to the renal damage ( 14 ). At present, some drugs have been confirmed by experiments that influence the protein expression in renal tissues interacting with infiltrated immune cells could improve DKD fibrosis ( 15 ), which provides new therapeutic strategies for the treatment of DKD.…”
Section: Introductionmentioning
confidence: 99%
“…DNA, histones, and antimicrobial proteins are found in NETs, which are produced by activated neutrophils, and high concentrations of NETs around pathogens are considered antibacterial. NETs play an important role in host defense mechanisms and in non-infectious diseases, such as autoimmune diseases, vasculitis, psoriasis and other pathological processes, including coagulation, thrombosis [2,3], diabetes mellitus [4], atherosclerosis [5,6], cystic fibrosis [7] and malignant tumors [8,9]. Furthermore, elevated levels of NETs have been detected in tissues of patients with PF, and they are associated with disease progression [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hyper NETosis or ineffective clearance of NETs would likely contribute to the pathogenesis of immune-related diseases ( 8 ). NETs are involved in numerous pathological processes, including infection ( 9 ), autoimmune diseases ( 10 ), tumor development ( 11 ), Alzheimer’s disease ( 12 ), acute ischemic stroke ( 13 ), peripheral nerve injury ( 14 ) and thrombosis ( 8 ). However, its role in neuroimmune diseases remains unclear.…”
Section: Introductionmentioning
confidence: 99%